Effects of a Single Dose of a Creatine-Based Multi-Ingredient Pre-workout Supplement Compared to Creatine Alone on Performance Fatigability After Resistance Exercise: A Double-Blind Crossover Design Study - Negro, Massimo; Cerullo, Giuseppe; Perna, Simone; Beretta-Piccoli, Matteo; Rondanelli, Mariangela; Liguori, Giorgio; Cena, Hellas; Phillips, Stuart M.; Cescon, Corrado; D’Antona, Giuseppe (Frontiers in Nutrition, 2022)
Background This study aims to investigate the acute effects of a single oral administration of a creatine-based multi-ingredient pre-workout supplement (MIPS) on performance fatigability and maximal force production after a resistance exercise protocol (REP). Methods Eighteen adult males (age: 23 ± 1 years; body mass: 76.4 ± 1.5 kg; height: 1.77 ± 0.01 m) were enrolled in a randomized, double-blind, crossover design study. Subjects received a single dose of a MIPS (3 g of creatine, 2 g of arginine, 1 g of glutamine, 1 g of taurine, and 800 mg of β-alanine) or creatine citrate (CC) (3 g of creatine) or a placebo (PLA) in three successive trials 1 week apart. In a randomized order, participants consumed either MIPS, CC, or PLA and performed a REP 2 h later. Before ingestion and immediately after REP, subjects performed isometric contractions of the dominant biceps brachii: two maximal voluntary contractions (MVCs), followed by a 20% MVC for 90 s and a 60% MVC until exhaustion. Surface electromyographic indices of performance fatigability, conduction velocity (CV), and fractal dimension (FD) were obtained from the surface electromyographic signal (sEMG). Time to perform the task (TtT), basal blood lactate (BL), and BL after REP were also measured. Results Following REP, statistically significant (P < 0.05) pre–post mean for ΔTtT between MIPS (−7.06 s) and PLA (+0.222 s), ΔCV slopes (20% MVC) between MIPS (0.0082%) and PLA (−0.0519%) and for ΔCV slopes (60% MVC) between MIPS (0.199%) and PLA (−0.154%) were found. A pairwise comparison analysis showed no statistically significant differences in other variables between groups and condition vs. condition. Conclusion After REP, a creatine-enriched MIPS resulted in greater improvement of sEMG descriptors of performance fatigability and TtT compared with PLA. Conversely, no statistically significant differences in outcomes measured were observed between CC and PLA or MIPS and CC.